2008
DOI: 10.2903/j.efsa.2008.745
|View full text |Cite
|
Sign up to set email alerts
|

Flavouring Group Evaluation 86, (FGE.86) - Consideration of aliphatic and aromatic amines and amides evaluated by JECFA (65th meeting) - Scientific Opinion of the Panel on Food Additives - Flavourings, Processing Aids and Materials in Contact with Food

Abstract: The present consideration concerns 35 aliphatic and aromatic amines and amides evaluated by the JECFA (65 th meeting). The Panel concluded that no corresponding FGE is available.Further two substances were evaluated by the JECFA in this group, but these are not in the Register (1-amino-2-propanol and acetamide; JECFA-no: 1591 and 1592, respectively).The Panel agreed with the application of the Procedure as performed by the JECFA for 28 of the 35 substances. The JECFA concluded the five substances 14.003, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The European Food Safety Authority (EFSA) has evaluated the use of piperine as a flavouring substance. In its evaluations, EFSA (2008;2011;2015) disagreed with a No Observed Effect Level (NOEL) of 20 mg piperine/kg bw/day that had previously been identified by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) (2006), due to the shortcomings of the underlying animal study (lack of histopathology, study duration) and in 2015 identified a No Observed Adverse Effect Level (NOAEL) of 5 mg piperine/kg bw/day, based on a newly available 90-day rat feeding study performed according to OECD guideline 408 (endpoint: dose-dependent increase in cholesterol level in male animals) [29,32,[48][49][50] (see (2) in Section 4.2.2). In its final conclusion, EFSA (2015) agreed with the JECFA (2006) conclusion "no safety concern at estimated levels of intake as flavouring substance" based on the MSDI approach (estimated European per capita intake by the MSDI approach: 6.2 µg piperine/day) [32,50].…”
Section: Information Based On Evaluations By Scientific Bodies and National Authoritiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The European Food Safety Authority (EFSA) has evaluated the use of piperine as a flavouring substance. In its evaluations, EFSA (2008;2011;2015) disagreed with a No Observed Effect Level (NOEL) of 20 mg piperine/kg bw/day that had previously been identified by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) (2006), due to the shortcomings of the underlying animal study (lack of histopathology, study duration) and in 2015 identified a No Observed Adverse Effect Level (NOAEL) of 5 mg piperine/kg bw/day, based on a newly available 90-day rat feeding study performed according to OECD guideline 408 (endpoint: dose-dependent increase in cholesterol level in male animals) [29,32,[48][49][50] (see (2) in Section 4.2.2). In its final conclusion, EFSA (2015) agreed with the JECFA (2006) conclusion "no safety concern at estimated levels of intake as flavouring substance" based on the MSDI approach (estimated European per capita intake by the MSDI approach: 6.2 µg piperine/day) [32,50].…”
Section: Information Based On Evaluations By Scientific Bodies and National Authoritiesmentioning
confidence: 99%
“…In its assessment of piperine as a flavouring agent, JECFA (2006) concluded regarding genotoxicity that piperine belongs to a group of aliphatic and aromatic amine and amide derivates for which negative results were reported in bacterial assays for reverse mutation and that piperine consistently gave negative results in a variety of in vivo studies [50,[52][53][54]. EFSA agreed in its assessment with JECFA that the available studies on genotoxicity did not preclude the evaluation of piperine (and some other aliphatic and arylalkyl amines and amides) as a flavouring agent [32,48,49].…”
Section: Potential Hazards 421 Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation